The Persuasive Effects of Partisan Campaign Mailers. (September 2014) - Doherty, David; Adler, E. Scott
A substantial literature has used field experiments to assess the mobilization effects of non-partisan mailers. However, little work has examined whether partisan mailers affect voters as intended. We report findings from two field experiments conducted in cooperation with partisan campaign strategists that allow us to assess the effects of negative and positive mailers. We find that mailers can affect voters—particularly their recognition of candidate names and their intent to turn out to vote. Notably, we find evidence that both negative and positive mailers stimulate intent to turn out.